Assessing potential factors leading to perioperative peri-implant fracture in femoral pertrochanteric fracture osteosynthesis using the proximal femoral nail antirotation 2: A retrospective study - Jiun-Jen Yang; Yung-Heng Hsu; Ying-Chao Chou; Ping‑Jui Tsai; Chang-Heng Liu; Yi-Hsun Yu (BMC Musculoskeletal Disorders)
Abstract Background Perioperative peri-implant fractures (PPIFs) pose infrequent yet significant challenges in orthopedic surgery, particularly in the context of femoral pertrochanteric fractures (FPF) treated with proximal femoral nail antirotation 2 (PFNA-2) nails. PPIFs can lead to prolonged recovery and may necessitate re-osteosynthesis in severe cases. Despite the effectiveness of PFNA-2 in the management of FPFs, our understanding of PPIFs in this specific context remains limited. This study aimed to elucidate the factors contributing to PPIFs in patients with PFNA-2-treated FPF. Methods In this retrospective analysis spanning from 2019 to 2022, patients with FPF treated with PFNA-2 nails were examined. Demographic data, fracture characteristics, and radiological parameters were collected, along with details of the PPIF management strategies and rehabilitation protocols. Radiological assessments included femoral morphology measurements and reduction and fixation quality evaluation. The area under the curve (AUC) was analyzed in this specific group. Results Among 157 patients, 3.2% experienced acute PPIFs managed conservatively with successful union without secondary surgical intervention. Younger age and increased femoral isthmus diameter (DI) emerged as significant predictors of PPIFs in the univariate regression analyses (P = 0.01). The AUCs for age (65.5 years) and DI (1.4 cm) were 0.78 and 0.79, respectively, indicating moderate accuracy. Conclusions Although PFNA-2 nails are reliable in managing FPFs, the persistence of PPIFs emphasizes their complex causes. This study highlights that younger age and increased femoral DI are crucial factors for PPIF occurrence in patients with PFNA-2-treated FPF. Conservative treatment with delayed weight-bearing ambulation may be effective in treating these fractures.